A systematic literature review of data-driven decision making: professional development program and its impact in enhancing teachers efficacy - Nisa, Aulia Zahratun; Kurniawati, Farida (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This article aims to collect, evaluate, integrate, and present the discussed articles to understand how professional development programs can enhance teachers' efficacy in implementing data-driven decision-making (D3M). Currently, many teachers have not applied D3M in their classrooms, even though D3M can help teachers develop effective teaching methods in class. One reason for this is the lack of teachers' efficacy in applying D3M. Therefore, this article includes several articles focused on professional development programs to improve teachers' efficacy in implementing data-driven decision-making in the classroom. This article uses a systematic literature review, specifically the PRISMA model, to select articles that meet the inclusion criteria based on the aforementioned topic. The findings show that the dimensions of efficacy, namely mastery experience, vicarious experience, verbal persuasion, and physiological and emotional states, are influenced when a program is designed with a focus on the content to be discussed, uses active learning methods, aligns with existing policies, offers sufficient duration, and fosters collective participation. Mastery experience can be enhanced through the content provided, active learning, and the appropriate duration of training. Verbal persuasion can emerge through the active learning process. Meanwhile, vicarious experience can be created through active learning methods, collaborative participation, and long program durations. When these three dimensions are met, individuals' physiological and emotional states will also improve. Learning through active learning and program duration are crucial aspects for enhancing teachers' efficacy after receiving a professional development program. Thus, professional development programs can be an effective way to increase teachers' efficacy in implementing D3M.